2018
DOI: 10.35360/njes.439
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspectives on English medium instruction: A survey-based study at a Norwegian university

Abstract: Internationalisation of higher education (HE) has led to an extensive implementation of English medium instruction (EMI) in Nordic higher education. This study explores students' attitudes towards EMI in the Norwegian study context. A total of 346 students within the fields of law, philosophy, and natural science responded to a questionnaire and evaluated statements concerning the language use in the educational context. Indexes measuring confidence in English skills and attitudes towards EMI were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
2
2
0
5
Order By: Relevance
“…Our findings are in line with those of Bukve (2018) who concluded that students with high proficiency in English had more positive attitudes towards English than those with low proficiency. These results are in the same vein with the results obtained for Pakistan, China and European states, where the students expressed worries that their academic English skills might not meet curricula expectations, which will negatively affect their school performance (Brock-Utne, 2001;Haidar & Fang, 2019;Hultgren et al, 2014;Jensen & Thogersen, 2011;Wilkinson, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with those of Bukve (2018) who concluded that students with high proficiency in English had more positive attitudes towards English than those with low proficiency. These results are in the same vein with the results obtained for Pakistan, China and European states, where the students expressed worries that their academic English skills might not meet curricula expectations, which will negatively affect their school performance (Brock-Utne, 2001;Haidar & Fang, 2019;Hultgren et al, 2014;Jensen & Thogersen, 2011;Wilkinson, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…This finding runs against the findings of Bouhmama and Bouhmama (2015) which indicated that Kuwait University female students had a less favorable attitude towards EMI compared to male students. However, the finding is in agreement with studies in places like Turkey, Norway, and Japan where females were found to have more positive attitudes towards EMI and English use in many domains of interaction (Brown & Sachdev, 2009;Bukve, 2018;Ernesto Macaro & Akincioglu, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…This sum score was normalized to a 1-5 scale. The indexes, which were developed in a previous paper (Bukve, 2018) are composite measures that represent certain theoretical concepts. Variables included in the indexes represent similar but not identical aspects of attitudes towards language skills and language use.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Scientists from different countries emphasise advantages of using EMI in education, showing that this concept contributes to internationalisation of the society, helps in the implementation of academic mobility, and most importantly provides an opportunity for the development of communication and management skills, creating conditions for active interaction of students. However, EMI is an insufficiently studied phenomenon and has several shortcomings identified by researchers, which are as follows: a low level of foreign language proficiency does not allow students to fully assimilate the material on the taught discipline; the low academic performance of students in the discipline with EMI demotivates them to learn the language; currently a small number of high-quality manuals and courses using EMI are presented [35][36][37]. Nevertheless, this concept is worth further consideration and implementation in the system of engineering personnel training, as it can contribute to the development of soft skills while learning a foreign language.…”
Section: Discussionmentioning
confidence: 99%